Austerity "versus" Diversity: the Production of News Content in Televisión del Principado de Asturias - Azahara Cañedo (Communication & Society (Formerly Comunicación y Sociedad), 2019)
Televisión del Principado de Asturias (TPA) is a regional public television that has been operating in Spain since 2005 by outsourcing part of its broadcasting activities. From the perspective of the political economy of communication and culture, this article studies the evolution of TPA’s outsourcing model, taking into account the production of news content. The time of the analysis extends from the start of its broadcasting to its last tender in this respect, in 2016. Initially, with the goal of promoting the regional audiovisual sector, TPA implemented a contracting model divided into content batches that were allocated to various companies, mostly regional. By doing so, the activities of production were distributed into different territorial areas. However, after the economic crisis of 2008, the confluence of several factors (economic austerity measures, the political change in the regional government and a torrent of lawsuits for illegal transfer of workers) changed the outsourcing model. Currently, the complete activity of production is concentrated on a sole tenderer, which is part of an audiovisual conglomerate at the national level, selected because of proposing the most advantageous economic offer. This has represented a reduction in the diversity of sources of production contracted and the triumph of an economic mindset over social benefit and public service in the socio-economic contexts of austerity.